An fMRI study of affective perspective taking in individuals with psychopathy: imagining another in pain does not evoke empathy - Decety, Jean; Chen, Chenyi; Harenski, Carla; Kiehl, Kent A. (Frontiers in Human Neuroscience, 2013)
While it is well established that individuals with psychopathy have a marked deficit in affective arousal, emotional empathy, and caring for the well-being of others, the extent to which perspective taking can elicit an emotional response has not yet been studied despite its potential application in rehabilitation. In healthy individuals, affective perspective taking has proven to be an effective means to elicit empathy and concern for others. To examine neural responses in individuals who vary in psychopathy during affective perspective taking, 121 incarcerated males, classified as high (n = 37; Hare Psychopathy Checklist-Revised, PCL-R ≥ 30), intermediate (n = 44; PCL-R between 21-29), and low (n = 40; PCL-R ≤ 20) psychopaths, were scanned while viewing stimuli depicting bodily injuries and adopting an imagine-self and an imagine-other perspective. During the imagine-self perspective, participants with high psychopathy showed a typical response within the network involved in empathy for pain, including the anterior insula, anterior midcingulate cortex, supplementary motor area, inferior frontal gyrus, somatosensory cortex, and right amygdala. Conversely, during the imagine-other perspective, psychopaths exhibited an atypical pattern of brain activation and effective connectivity seeded in the anterior insula and amygdala with the orbitofrontal cortex and ventromedial prefrontal cortex. The response in the amygdala and insula was inversely correlated with PCL-R factor 1 (interpersonal/affective) during the imagine-other perspective. In high psychopaths, scores on PCL-R Factor 1 predicted the neural response in ventral striatum when imagining others in pain. These patterns of brain activation and effective connectivity associated with differential perspective-taking provide a better understanding of empathy dysfunction in psychopathy, and have the potential to inform intervention programs for this complex clinical problem.